Patient Characteristics and Outcomes Following Establishment of a Living Donor Kidney Transplant Program in Sub-Saharan Africa. (July 2018) - Gelan, Engida; Leitchman, Alan; Tedela, Faski; Punch, Jeffery D.; Woodside, Kenneth; Bekele, Mahteme; Tadese, Mekdim; Abate, Mersema; Ahmed, Momina; Seyum, Assefa; Berehe, Teklebirhan; Abebe, Zerihun; et al.
Abstract : Background: End-stage renal disease (ESRD) is one of the most common non-communicable causes of death. ESRD's effects are significantly worse in the economically underprivileged parts of African society where renal replacement therapy such as dialysis or kidney transplantation is not available, as it is both scarce and unaffordable for most patients and families. About 2 years ago, we established Ethiopia's first living donor kidney transplant program. Herein, we sought to describe the patient characteristics and outcomes of our living donor kidney program. Methods: We retrospectively analyzed all ESRD patients who received kidney transplantation at the Ethiopian Ministry of Health National Kidney Transplant Center, located at St. Paul's Hospital Millennium Medical College in Addis Ababa. All patients underwent living donor kidney engraftment from September 2015 to August 2017. Results: After about 3 years of planning prior to human transplants, a total of 52 living donor kidney transplants were performed, of which 20 were performed in the first year. Of these, 40 recipients (76.9%) were male. Recipient age ranged from 16 to 60 years, with a mean of 34.5 years, and a mean BMI of 20.1 (range 15.3-30.6). Geographically, the majority of patients were from Addis Ababa (71.2%). Due to a relative lack of access for pre-transplant biopsy, the cause of ESRD was unknown in many patients (63.5%). All patients received left donor kidneys, and the majority was placed on the recipient's left external iliac artery (88.5%). The mean operation time and blood loss were 148 minutes and 120 mL, respectively. The mean length of stay was 8.1 days (SD=4.1). There were a total of 9 surgical complications (6 early and 3 late) in 7 patients, with superficial surgical site infection (SSI) being the most common (4). There were no patient deaths during the immediate postoperative period. Conclusions: We have successfully established the first kidney transplant center in Ethiopia. While training for faculty and staff are ongoing, our results so far are comparable to other international centers. Key words: ESRD, Kidney Transplant, Outcomes